Comparison of Electrical Conductivity in Compounds of Carbon Black With Natural and Butadiene Rubbers - Sancaktar, Erol; Basan, Satilmis (Frontiers in Materials, 2019)
Carbon black (CB) filled butadiene (BR) (Cis-1,4-polybutadiene) and natural (NR) (Cis-1,4-polyisoprene) rubber compounds containing 60–100 phr (per hundred) CB were investigated for their electrical conductivity under different loads over time. Due to their high deformability, the percolation thresholds for CB–BR and CB-NR compounds were shown to be functions of compression loads applied on them. Conductivity of such compounds increased with time and compressive load levels applied. Rheological experiments involving evaluations of the storage moduli, G´, as well as the loss moduli, G´´ and the dynamic viscosities, η* for the compounds were performed to assess rate dependence of the compounds’ conductivity under compressive loads. The storage and loss moduli values for both the CB-BR and the CB-NR compounds decreased with increasing strain levels. Thus, the rate of decrease in resistivity is expected to increase at higher strain (higher pressure) levels. Furthermore, the storage moduli increased monotonically with increasing frequency (rate), and thus, we expect the rate of decay in resistivity to be lower at higher rates of pressure application. Comparison of variations in conductivity between the CB–BR and CB-NR compounds as functions of time and pressure, however, revealed that, overall, the conductivity levels are also strongly dependent on the nature of the molecular structure of these rubber materials and their initial interactions with CB during compounding and the resulting dispersion levels of CB. Once such dispersion structure is established, the overall difference in conductivity levels for the CB–BR and CB-NR compounds remain approximately unchanged for given time and pressure conditions for the cases where high CB fill levels (~90 phr) are used and asymptotic conductivity values are reached. The experimental results revealed that because of the presence of higher number (approximately two-fold) of hydrogen side atoms on the linear BR chains, CB–BR compound forms more physical crosslinks (mostly due to hydrogen bonding) in comparison to the CB-NR compound resulting in more effective CB dispersion and higher conductivity. Such higher efficiency in CB dispersion and percolation in BR is further implied by higher conductivities despite higher G´ and η* values for the CB–BR compound in comparison to the CB-NR compound.